MEMBANGUN BUDAYA INOVATIF DI ORGANISASI PUBLIK : STRATEGI DAN TANTANGANNYA - Arrazak, Muhammad Afdhal; Frinaldi, Aldri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In facing the development of the era and the increasingly complex needs of society, public organizations need to build an innovative culture so that they can be more responsive and adaptive. This article aims to describe the strategies and challenges in building an innovative culture in public organizations. The method used in this study is a library research by collecting data from various reading materials that are relevant to the topic and objectives of the study. The results of this study indicate that there are several strategies that can be carried out in building an innovative culture in public organizations, namely leadership that encourages innovation, a collaborative work environment and awards and incentives for innovation. In addition to strategies, there are also several challenges in building an innovative culture in public organizations including rigid bureaucracy, resistance to change and limited resources and support.